Meta-analysis reveals negative responses of freshwater organisms to the interactive effects of pesticides and warming - de Souza, Cristiane Marinho [UNESP]; Massi, Klécia Gili [UNESP]; Rodgher, Suzelei [UNESP] (Springer Nature, 2023)
Pesticides are among the pollutants present in aquatic bodies. Climate change is expected to favor the growth, multiplication, persistence, and range expansion of most serious agricultural pests. In addition, due to climate change and land degradation, pest species may become more abundant, with consequent losses in agricultural production and, thus, pesticide use is likely to intensify. Temperature variations and thermal extremes caused by climate change may have profound implications for pesticide toxicity in aquatic organisms. Using a meta-analytic technique to the peer-reviewed literature, we evaluated the impacts of warming and pesticides in isolation and combination on the biological responses of freshwater biota (microalgae, invertebrates and vertebrates). Meta-analysis of the dataset showed that the association between pesticides and temperature showed more negative effects on the fitness and physiological regulation of organisms than on the isolated effects of variables. In contrast, the independent effect of pesticides affected negatively only the fitness measurements, while molecular responses were positively influenced by temperature, and physiological regulation was negatively influenced by temperature increase. Microalgae and invertebrates were the groups most negatively affected by the interaction of pesticides (atrazine, avermectin – imidacloprid, chlorpyrifos) and temperature (25 °C, 30 °C). Additional studies should consider other factors relevant to climate events in freshwater that can presumably interact with chemicals, to make more exact generalizations about chemical contamination and climate change.
Keywords: Aquatic biota; Climate change; Meta-analysis; Pollutant